2021
DOI: 10.1088/1755-1315/852/1/012089
|View full text |Cite
|
Sign up to set email alerts
|

Study of New Technologies for Cultivation of Solanaceous Vegetable Crops in Short Vegetation Period Regions of Armenia

Abstract: The article considers the impact of new integrated technologies (mulching, drip irrigation, use of wooden sticks for each plant, use of new biofertilizers in the cultivation of solanaceous vegetable crops (tomato, pepper, eggplant) in regions with a short growing season. The study of new technologies in the cultivation of solanaceae crops in regions of short vegetation period shows the effectiveness of the impact of these technologies on the biological characteristics, economic-valuable and qualitative indicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 6 publications
1
7
0
Order By: Relevance
“…The results of the research have shown that cultivation conditions, technologies, the use of fertilizers, irrigation systems contribute to the morphological indicators of cultivated and wild types of tomato plants, fruit weight, leaf size. [9][10][11][12][13][14][15]. Our studies revealed that the morphological indicators of the seedlings of a number of tomato samples, starting from mass germination and moving to the open field.…”
Section: Resultsmentioning
confidence: 65%
“…The results of the research have shown that cultivation conditions, technologies, the use of fertilizers, irrigation systems contribute to the morphological indicators of cultivated and wild types of tomato plants, fruit weight, leaf size. [9][10][11][12][13][14][15]. Our studies revealed that the morphological indicators of the seedlings of a number of tomato samples, starting from mass germination and moving to the open field.…”
Section: Resultsmentioning
confidence: 65%
“…[23][24][25][26][27]. Several researchers [28][29][30] in their research came to the realization that the conditions of plant cultivation, ecology, and the use of different amounts of fertilizers contribute to the increase of bioactive properties in fruits, and the improvement of antioxidant properties. All this contributes to growing healthier food and making it available to the masses [31][32][33][34][35][36].…”
Section: Discussionmentioning
confidence: 99%
“…The solution of "Bio mix 1" fertilizer was also applied during the pre-sowing tillage of greenhouse ground and after a month of its application the 55-day tomato and pepper seedlings (90+60x50cm planting pattern) and 30-day seedlings of cucumber (90+60x40 cm planting pattern) were transplanted in the ground. The trials were set up in three replications [5][6] The plants treatment was organized in line with the accepted methodology [7].…”
Section: Methodsmentioning
confidence: 99%